Review of Practicing Privacy Literacy in Academic Libraries: Theories, Methods, and Cases - Kevin Adams (Journal of New Librarianship, 2024)
Librarians and students alike find themselves living in a world where maintaining their digital privacy feels nearly impossible. Alaxandria Chisholm and Sarah Hartman-Caverly open one of their workshops asking attendees to consider where they have recently left data tracks. Answers might include map apps, dating apps, workout apps, streaming websites, or even library databases. These tracks create data shadows that are used for advertising, training algorithms, and even creating data dossiers that can be sold to law enforcement. There is an inherent tension between the commitment to privacy that librarians hold as a core value and the academic library’s drive to integrate new technologies. As libraries have pushed the line of privacy by engaging with social media, negotiating contracts with database vendors that collect patron data, and participating in learning analytics, academic librarians are increasingly aware of the existential threat posed by what Shoshana Zuboff calls surveillance capitalism. As librarians seek to educate themselves to better understand the ways in which the traditional library commitment to privacy fits into increasingly omnipotent government, corporate, and now academic surveillance apparatuses, librarians are faced with feelings that are commonly expressed by patrons and students regarding privacy: overwhelm and resignation. In Practicing Privacy Literacy in Academic Libraries, an edited volume, editors Chisholm and Hartman-Cavalry successfully capture the urgency that the existential threat of surveillance structures pose to humanity, while presenting work that will allow librarians to start contemplating and integrating privacy into their professional practice. Central to Chisholm and Hartman-Caverly’s edited volume is a human focused approach that follows their teaching philosophy: “privacy is about respect for persons, not about protecting data.” (x)